PERAN JOB SATISFACTION SEBAGAI MEDIATOR ORGANIZATIONAL COMMITMENT DAN EMPLOYEE ENGAGEMENT TERHADAP TURNOVER INTENTION PEKERJA MILENIAL DI INDUSTRI HOSPITALITY - Sumiyarsih, Sumiyarsih; Wahyuningsih, Tri Harsini; Suprapto, Yetti Luttiyan; Susanto, Djaelani (Jurnal Manajemen, 2024)
This research aims to examine the influence of organizational commitment and employee engagement on turnover intention, both directly and indirectly, among millennial workers in the hospitality industry. The independent variables in this study are organizational commitment and employee engagement. Turnover intention as the dependent variable and job satisfaction as the mediating variable. A sample of 300 respondents was taken purposively from millennial generation workers in the hospitality industry, especially hotels. Data was collected using a questionnaire distributed online via social media by sharing a google form link with target respondents. After the data was collected, the Hayes macro model regression analysis was carried out using the SPSS process to carry out hypothesis testing. After testing, the results showed that organizational commitment and job satisfaction had no effect on turnover intention, while employee engagement had a direct effect on turnover intention. Apart from testing turnover intention, testing was also carried out on the job satisfaction variable as a dependent variable. The results prove that organizational commitment and employee engagement have a positive effect on job satisfaction. However, job satisfaction is proven not to mediate the influence of organizational commitment and employee engagement on turnover intention of millennial workers in the hospitality industry.